A Study for the Prediction of the Social Anxiety Level of University Students Through Emotional Intelligence Features - (:unkn) unknown (My University, 2020)
The main aim of this study is to determine the power of emotional intelligence and demographiccharacteristics of the university students studying in various departments (nmale = 54, nfemale = 149, ntotal = 203) topredict their social anxiety levels. The study was conducted with a predictive correlational survey model. LeibowitzSocial Anxiety Scale (LSAS), Emotional Intelligence Test (BarON-EQ), and demographic information form wereused to collect data. Sub-objectives were examined by ANOVA and independent samples t-test followed by posthoc analysis. Stepwise regression analysis was used for the predictive power of BarON-EQ test scores to predictSocial Anxiety scores. Among the Emotional Intelligence scores, significant results were obtained in favor of femalesfor Interpersonal Relations total scores, Empathy and Social Responsibility subscale scores, and in favor of malesfor Independence and Stress Management scores. According to the progressive regression analysis for the Bar'OnEQ-i test, Assertiveness and Independence scores within the scope of the “Person-Specific” dimension can predictsocial anxiety by 18%, and also interpersonal relations and social responsibility scores within the scope ofinterpersonal components can predict social anxiety by 9%.

Araştırmanın temel amacı, çeşitli bölümlerde öğrenim gören üniversite öğrencilerinin (nerkek=54, nkız=149, ntoplam= 203) duygusal zekâ ve demografik özelliklerinin, sosyal anksiyete düzeylerini yordama gücünü belirlemektir. Araştırma ilişkisel tarama modelinde yordayıcı korelasyonel bir çalışmadır. Leibowitz Sosyal anksiyete ölçeği (LSAS) , Duygusal Zekâ Testi (BarON-EQ ) ve demografik bilgi formu veri toplama aracı olarak kullanılmıştır. Alt amaçlar Tek yönlü varyans analizi (ANOVA) ve ilişkisiz gruplar t testi ile takiben post-hoc analizlerle incelenmiştir. BarON-EQ test puanlarının Sosyal Anksiyete puanlarını yordama gücü için adımsal regresyon analizi kullanılmıştır. Duygusal zekâ puanlarından Kişilerarası İlişkiler toplam, Empati ve Sosyal Sorumluluk alt ölçek puanları kızların lehine; Bağımsızlık ve Stres Yönetimi puanları için de erkekler lehine anlamlı sonuç elde edilmiştir. Bar’On EQ-i testi için yapılan aşamalı regresyon analizine göre “Kişiye Özgü” boyutu kapsamındaki Girişkenlik ve Bağımsızlık puanları sosyal kaygıyı % 18 oranında, ayrıca kişiler arası bileşenler kapsamındaki Kişilerarası İlişkiler ve Sosyal Sorumluluk puanlarının sosyal kaygıyı % 9 oranında yordayabilmektedir
Üniversite Öğrencilerinin Duygusal Zekâ Özelliklerinin Sosyal Kaygı Düzeyini Tahminine Yönelik Bir Çalışma